The infernal machine : a true story of dynamite, terror, and the rise of the modern detective - Johnson, Steven, 1968- (Crown, 2024)
"A riveting account of the anarchists who terrorized the streets of New York-and the detective duo who transformed policing to meet the threat-from the bestselling author of The Ghost Map"--